IMPLEMENTASI NILAI-NILAI PANCASILA SEBAGAI STRATEGI PEMBANGUNAN KARAKTER BANGSA DI ERA GLOBALISASI - Riswati Ashifa; Dinie Anggraeni Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study is to provide an overview of the values ​​of Pancasila as a national character development strategy in the era of globalization, whether they have been implemented properly or not. The research method that I use in this research uses non-interactive qualitative methods. The results of this study indicate that character building has been carried out by all means, but until now it has not been implemented optimally. This can be seen from the large economic, political and social disparities, unjust rule of law, corruption, collusion and nepotism that spread to all sectors. Seeing the dire situation and condition of the nation's character, our government took the initiative to prioritize the character building of the Indonesian nation. This can be seen from the national development mission itself which consists of eight missions and character education is the first mission in realizing the vision of national development.